Similitud del lactato y frecuencia cardiaca en test específico y en competencia de Lucha Libre - Nicot Balón, R. G.; Ríos Hernández, A. N.; Quevedo Espinoza, C. V. (Revista Cubana de medicina del deporte y la cultura fisica, 2019)
Changes in combat time and pauses in wrestling have led to changes in sports training and the tests carried out for their control. There are specific terrain tests, but it is unknown how much they differ from the outcome in the combat. The objective of this work was to determine the behavior of pedagogical and biomedical variables through a specific test applied in male wrestling and the level of similarity with the combat. An observational, retrospective study was carried out. The sample was made up of 10 prioritized elite athletes. They were studied in two moments of the preparation of a macrocycle: during the performance of a specific test the 2 x 3 test and during the national closing championship of the first macrocycle. Mean comparison studies of the different biological variables were performed using the analysis of variance and Sheffe post hoc test (?=0.05). Favorable variations of the pedagogical and biomedical indicators of the athletes between stages in the analyzed test are confirmed. The recovery of the heart rate of the athletes was adequate at the time of their preparation, but not the recovery of lactacidemia that showed low aerobic development. It is shown that the 2x3 test specific to this sport demo strates similarity with the competition.